Case Report: Off-Label Use of Omalizumab in a 6-Year-Old Boy With ASD Ameliorated Severe Allergic Rhinitis and Subsequently Improved Behavioral Symptoms - Kong, Xue-Jun; Clairmont, Cullen; Wang, Bryan (Frontiers in Pediatrics, 2021)
The severity of allergic symptoms can exacerbate behavioral problems in children with ASD. Omalizumab, an anti-IgE antibody, has previously shown efficacy in treating allergic rhinitis and behavioral problems in a 12-year-old child with ASD. The present case report provides robust characterization of behavioral improvement in a 6-year-old child with ASD, allergic rhinitis, and autoimmune disorder. A 6-year-old boy with ASD and Hashimoto's disease presented to the clinic with severe allergic rhinitis, irritability, and language delay. After other treatments failed to improve symptoms, our patient was treated with omalizumab at 300mg/month via subcutaneous injection for a total of 6 months. Marked improvement in allergic symptoms were observed at 2 months into treatment and were maintained through the treatment period. At the conclusion of the treatment period, results from multiple behavioral questionnaires, including the SRS-2, ABC, RBS-R, and PSQI, demonstrated substantial improvement in ASD-related behavioral symptoms. In this case, omalizumab markedly improved ASD-related and sleep behavior in a 6-year-old with ASD, allergic rhinitis, and autoimmune disorder. Future studies with larger patient populations are warranted to investigate the efficacy of omalizumab in patients with ASD and allergy symptoms.